A Long-Term Lens: Cumulative Impacts of Free-Roaming Cat Management Strategy and Intensity on Preventable Cat Mortalities - Boone, John D.; Miller, Philip S.; Briggs, Joyce R.; Benka, Valerie A. W.; Lawler, Dennis F.; Slater, Margaret; Levy, Julie K.; Zawistowski, Stephen (Frontiers in Veterinary Science, 2019)
This study used a previously developed stochastic simulation model (Miller et al. 2014) to estimate the impact of different management actions on free-roaming kitten and cat mortality over a 10-year period. These longer-term cumulative impacts have not been systematically examined to date. We examined seven management scenarios, including: 1) taking no action, 2) low-intensity removal, 3) high-intensity removal, 4) low-intensity episodic culling, 5) high-intensity episodic culling, 6) low-intensity trap-neuter-return (TNR), and 7) high-intensity TNR. For each scenario we tracked within the model the number of kittens born, the number of kittens surviving to adulthood, and the number of adults removed using lethal control over the entire 10-year simulation. We further defined all kitten deaths and lethal removal of adults as “preventable” deaths because they could potentially be reduced by certain management actions. Our simulation results suggested that the cumulative number of preventable deaths over 10 years for an initial population of 50 cats is highest for a “no-action” scenario, estimated at 1,000 deaths. It is lowest for a high-intensity TNR scenario, estimated at 31 deaths, a 32-fold difference. All management scenarios tested, including removal and culling, produced fewer predicted preventable deaths than a no-action scenario. For all management scenarios, the higher-intensity option (defined in terms of the proportion of animals sterilized or removed within a given time period) led to fewer preventable deaths over time than the lower-intensity option. Based on these findings, we concluded that management intensity is important not only to reduce populations more quickly, but also to minimize the number of preventable deaths that occur over time. The lessons for the animal welfare community are both encouraging and cautionary. With sufficient intensity, management by TNR offers significant advantages in terms of combined lifesaving and population size reduction. At lower intensity levels, these advantages are greatly reduced or eliminated. We recommend that those who seek to minimize suffering and maximize lifesaving for free-roaming cats attempt to balance prospective goals (i.e., saving lives tomorrow) with proximate goals (i.e., saving lives today), and recognize that thoughtful choice of management strategies can ensure that both of these complementary goals are achieved.